THE ROLE OF KOMINFO LUWU IN EDUCATING PREVENTION OF HOAX (International Conference on Social and Islamic Studies, 2022)
This research is to find out the education that is carried out by the Luwu Communications and Informatics Service and the obstacles encountered in preventing the spread of hoax information among the District Community of Luwu. Research using descriptive qualitative research with data sources and in-depth interviews. Inside informant research, namely the Head of the Luwu District Communication and Informatics Service, Head of the Division Coding and Information Communication and Informatics Office of Luwu Regency, Head of Division Communication and Informatics Office of Kominfo Luwu Regency, and Founder of Media Digital Madrasah. The results of the study showed that the Regency Communications and Informatics Office Luwu has a pattern in educating the public. Role communicators as educators are carried out, and the community as communicants is given the understanding to prevent hoaxes. There are several mediums used in conducting education. But deep maximizing this pattern, the Luwu District Communication and Informatics Service has obstacles that result in less than optimal education in the middle of society. The blocks are obstacles. to communication, human resource barriers, and the last obstacle outreach budget.